2008
DOI: 10.1111/j.1744-7402.2008.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Toughness Enhancement for Alumina Systems: A Review

Abstract: Investigations have been carried out to determine ways of tailoring ceramic materials in order that one or more toughening mechanisms are activated in service. Microstructural manipulations, as well as composite formulations involving metallic, intermetallics, and ceramic phases have been used with ceramic matrices. Macrostructurally, laminated structures and functional gradient materials (FGMs) have also been formulated to enhance mechanical properties. Although significant improvements in material properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 82 publications
(86 reference statements)
0
46
0
1
Order By: Relevance
“…The magnitude of fracture toughness K IC attained in the studied materials is also reported in Table 1. For all studied cases, this strength parameter is superior to that of the pure alumina which is of about 3.2 MPa.m -1/2 [3] . Due to these fracture toughness values it can be concluded that the metallic particle´s dispersion into a ceramic matrix, as conducted in this work, may increase its toughness.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The magnitude of fracture toughness K IC attained in the studied materials is also reported in Table 1. For all studied cases, this strength parameter is superior to that of the pure alumina which is of about 3.2 MPa.m -1/2 [3] . Due to these fracture toughness values it can be concluded that the metallic particle´s dispersion into a ceramic matrix, as conducted in this work, may increase its toughness.…”
Section: Resultsmentioning
confidence: 74%
“…This is because cracks easily propagate in this ceramics and therefore they might cause unpredictably fail in service. The incorporation of several reinforcement materials such as; ceramics, metals and intermetallics compounds into an Al 2 O 3 matrix forming a composite material has been proved to be an effective experimental route to improve toughness of the ceramic matrix 3 . In consequence, they can be used, for example in application at high temperatures such as in the construction of gas turbine engines in order to increase their thermal cycle efficiency [4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…This improvement in fracture toughness is attributable to the incorporation into the ceramic matrix of a metal with high ductility such as silver. Several authors [1,11,13] have commented that the toughening mechanism in Al 2 O 3 /metals composites is due to plastic deformation of the metallic phase, which forms crack-bridging ligaments. Thus it is illustrated the significant effect on the fracture toughness of alumina the incorporation therein of small amounts of a ductile metal as silver.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…However, its applications as structural material have been limited principally by its low fracture toughness. Al 2 O 3 ceramics can be toughened with the incorporation of fine metallic particles [1], for this reason it has been prepared successfully some Al 2 O 3 -systems by different techniques such as: pressure-assisted thermal explosion [2], slip casting [3], metal infiltration [4][5][6], sintering high pressing [7], Chemical deposition [8], self-propagation high temperature synthesis [9] and reaction synthesized [10]. Nevertheless, most of these processes are costly and they are very complex in their procedures and control.…”
Section: Introductionmentioning
confidence: 99%
“…Th is is because cracks easily propagate in this ceramics and therefore they might fail unpredictably in service. Th e incorporation of several reinforcement materials such as; ceramics, metals and intermetallics into an Al 2 O 3 matrix forming a composite material has been proved to be an eff ective experimental route which improves toughness and mechanical strength of the composites matrix [3]. Th us, composites can be constituted in some cases of carbide ceramics, oxide ceramics and metals, and they can be used, for example in application at high temperatures such as in the construction of gas turbine engines in order to increase their thermal cycle effi ciency [4][5].…”
Section: Introductionmentioning
confidence: 99%